Fire Severity Causes Temporal Changes in Ground-Dwelling Arthropod Assemblages of Patagonian Araucaria–Nothofagus Forests - Vergara-Egert, P; Fierro-Tapia, C (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Fire is one of the main drivers of anthropogenic disturbances in temperate forest ecosystems worldwide, with multiple effects spread across ecological networks. Nevertheless, the biodiversity effects of fire are poorly known for species-diverse groups such as arthropods. In this research, we used a burn gradient generated two and three years after a large fire event to assess how different levels of fire severity affect arthropod diversity in the forest with the main forest forming long-living tree species Araucaria araucana, in southern Chile. The species richness and abundance of arthropods among trophic guilds was estimated annually in four fire-severity levels. We found that arthropods responded differently to fire severity levels, depending on their trophic guilds and years after fire (two and three years after fire). During the second year after fire, zoophages, phytophages, and parasitoids were more diverse in areas with high fire severity within the second year after fire, as compared to those in areas with low severity or unburned stands. In the third year after fire, a change in this trend was observed, where the abundance of all groups dropped significantly, with positive changes in the diversity in zoophages, phytophages, polyphages and saprophages, which is more noticeable in sites with high severity. These results indicate that annual variation in environmental conditions triggers bottom-up cascading effects for arthropods. Forests stands severely impacted by fires support highly fluctuating and possibly unstable arthropod assemblages. Hence, restoration efforts should be focused on recovering microhabitat conditions in these stands to allow the persistence of arthropods. © 2022 by the authors.